Corporate Commitments to Stakeholders over Time and Across Countries: A European Comparative Study (2000–2010) - Boncori, Anne-Laure; Braune, Eric; Mahieux, Xavier (Management international / International Management / Gestiòn Internacional, 2016)
Using social responsibility ratings on over 663 companies belonging to 18 European countries in 2000 and 2010, this paper examines to what extent stylized models of Corporate Governance (CG) shape national systems of CG and corporate commitments to stakeholders in the long run. In doing so, we question arguments in favor of convergence versus divergence. In particular, we assess the factors that explain these trends and the detected processes. Our findings are manifold but principally highlight the structuring dimension of both the shareholder-oriented and stakeholder-oriented models of CG, and the role of micro-economic factors in explaining the changing and varying corporate commitments.